2013
DOI: 10.2320/matertrans.md201210
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Thick Aluminum Wire during Ultrasonic Bonding

Abstract: The deformation behavior of thick Al wires and the expansion behavior of the bond area during ultrasonic wedge bonding to AlSi, Si and SiO 2 substrates were measured simultaneously in detail with a high-speed measuring system. The deformation of the wire by the application of the bonding force is completed immediately. The deformation restarts by the application of the ultrasonic vibration. The deformation induced by applying the bonding force consists of only elastic component, whereas that by ultrasonic vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…7,8) By only applying the same static pressure as that in USW, deformation of wire cannot be achieved in the ambient atmosphere and temperature without applying ultrasonic vibration, 8) showing that the slipping motion at interface is essential for sound USW joint. It has also been reported that the scrubbing action and compressive deformation can effectively disrupt hard oxide on a soft metal (such as 0.51 nm of Al 2 O 3 on Al) rather than soft oxides on harder metal (such as NiO on Ni).…”
Section: Introductionmentioning
confidence: 99%
“…7,8) By only applying the same static pressure as that in USW, deformation of wire cannot be achieved in the ambient atmosphere and temperature without applying ultrasonic vibration, 8) showing that the slipping motion at interface is essential for sound USW joint. It has also been reported that the scrubbing action and compressive deformation can effectively disrupt hard oxide on a soft metal (such as 0.51 nm of Al 2 O 3 on Al) rather than soft oxides on harder metal (such as NiO on Ni).…”
Section: Introductionmentioning
confidence: 99%
“…This often fluctuated, affected by the initial fixing situation. The bonding conditions of Fb = 7 N and Pu = 3 or 4 W adopted in the present study provide some fluctuation to the initial large sliding; however, these can provide stable bonding in the early, middle, and later stages [1,5,[22][23][24][25][26][27][28][29]36]. The friction slip was the dominant mechanism in the early stage.…”
Section: Discussionmentioning
confidence: 75%
“…Numerous on-line measurements and in-situ observations of temperature [3,10,18,21], interfacial frictional force (power) [9,21,[23][24][25][26][27], frictional slip (relative motion) at the bonding interface [3,9,23,24,28], ultrasonic vibration [21,[28][29][30], deformation behavior [29,31], contact resistance [32], and electrical signals from ultrasonic generators [33] during ultrasonic bonding have been performed. The on-line measurements and in-situ observations are extremely useful and informative for comprehension of ultrasonic microjoining.…”
Section: Introductionmentioning
confidence: 99%
“…Cu wires are used more often because of their low cost [11,12]. Al wires are used for wedge bonding [13][14][15]. In 2008, Al ribbon bonding began to be used for the power-electronics packaging of hybrid vehicles; e.g., insulated gate bipolar transistor modules [16].…”
Section: Introductionmentioning
confidence: 99%
“…This oxide-removing scrubbing can be facilitated by the friction slip due to ultrasonic vibration. The bond-formation in Al/Al UB needs the friction slip [14,15]. Experimental results based on transmission electron microscopy observation suggest that there was no oxide film at the central bond area [14].…”
Section: Introductionmentioning
confidence: 99%